Penerapan Digitalisasi Administrasi Hibah di Biro Kesejahteraan Rakyat Sekretariat Daerah Provinsi Jawa Timur - Zafira, Fadilla; Reviandani, Oktarizka (IAI Nasional Laa Roiba Bogor, 2025)
Digitalization has become a crucial element in transforming public services, aiming to enhance efficiency, transparency, and accountability. This study analyzes the implementation of the People's Welfare Bureau Grant Assistance Application (ABAH KESRA) developed by the People's Welfare Bureau of the Regional Secretariat of East Java Province. The system is designed to digitize the grant administration process, particularly through the independent upload feature for Accountability Reports (LPJ). Using a qualitative descriptive approach and analysis based on the Support, Capacity, and Value (SCV) framework, this study reveals that the successful implementation of the system is supported by leadership commitment, adequate technological infrastructure, human resource training, and user socialization. This innovation accelerates the reporting process, improves data accuracy, and facilitates grant fund monitoring. However, challenges such as uneven digital literacy and potential data security threats remain significant concerns. To address these challenges, strategic efforts such as intensive training, infrastructure development, and regular monitoring are essential. The implementation of ABAH KESRA not only fulfills the principles of ideal public service but also strengthens good governance and enhances public trust in the government.